Analisis Faktor-Faktor yang Mempengaruhi Tax Avoidance pada Perusahaan Properti dan Real Estate - Venny Carolina; Poniman Poniman (Komunitas Dosen Indonesia, 2023)
At present there are still many companies in Indonesia that carry out tax evasion and tax avoidance activities due to the large number of companies whose business activities are across countries. Companies that practice tax avoidance can cause managers to think about using the best profitable opportunities that aim to maximize tax avoidance in order to get the maximum profit as expected. Tax avoidance actions can result in state revenue being less than it should be. But on the other hand, tax avoidance does not violate the law and is permissible. The existence of governance in a company can influence the determination of policies for making corporate income tax payments. This study aims to analyze the influence of independent commissioners, institutional ownership and audit quality on tax avoidance. The population in this study are all property and real estate sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The technique in this study was carried out using a purposive sampling method and there were 13 companies that met certain criteria. The data used are annual reports from property and real estate sub-sector companies listed on the Indonesia Stock Exchange and processed using the SPSS version 26 program. The results of this study indicate that independent commissioners, institutional ownership and audit quality partially or simultaneously have no influence on tax avoidance.